RATTAN CRAFTSMANSHIP CENTER AND WOODWORKING KABUPATEN CIREBON - Karto Wijaya; Isti Qurani (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: Local cultural assets include the cultural wealth of an area, both in physical and non-physical aspects that grow and develop from generation to generation. Craftsmanship tends to have a fairly broad exploration of ideas in making works or products of their creation. Rattan as a local product that has become part of the body of the people of Cirebon Regency, especially the Galmantro Rattan Tourism Village. The activities and potentials in this village seem to give a